Desenvolvimento endógeno e territorialização da confecção de bordados em Sergipe - Sousa, Moacir Araujo de (2014)
The aim of this study was to analyze the territorialization of the manufacturing of embroidery in Sergipe, focusing on its relations to the labour networks, flows and subordination processes. To investigate the territorialization of embroidery in Sergipe involves analyzing the behaviors of the communities that are settled in the territories in which the embroidery is manufactured. Geography is used in this context as a scientific tool for understanding the differentiation of places, territories, and regions as products of the relationships among men themselves and between men and nature. Procedures of this study, based on the hypotheticaldeductive method, were divided into three stages: 1) desk job, 2) fieldwork, and 3) synthesis. The first step included a literature review, consulting companies related to embroidery (SEBRAE, SEDETEC, and Associations) and mapping. The second step included the use of questionnaires, interviews and photo records. The third stage corresponded to the data analysis. Results confirmed the hypothesis that the territorialization of the manufacturing of embroidery in the state of Sergipe, in the way it has been established over the years, favors the development of |territories of exploitation|. In these territories, socially and economically less favorable actors are dominated and exploited as abundant and cheap labour by actors who somehow stand out for having the economic, social and political means to the appropriation of the territory, using it for satisfying their needs.